Effects of sevelamer carbonate versus calcium acetate on vascular calcification, inflammation, and endothelial dysfunction in chronic kidney disease - Darius L. Mason; Kavitha Godugu; Daryl Nnani; Shaker A. Mousa (Wiley, 2022)
Abstract Hyperphosphatemia is present in most patients with end‐stage renal disease (ESRD) and has been associated with increased cardiovascular mortality. Phosphate binders (calcium‐based and calcium free) are the mainstay pharmacologic treatment to lower phosphorus levels in patients with ESRD. We evaluated biochemical markers of vascular calcification, inflammation, and endothelial dysfunction in patients with chronic kidney disease (CKD) treated with sevelamer carbonate (SC) versus calcium acetate (CA). Fifty patients with CKD (stages 3 and 4) were enrolled and assigned to treatment with SC and CA for 12 weeks. At the end of the study the biomarkers of vascular calcification, inflammation, and endothelial dysfunction were analyzed. A significant increase in HDL‐cholesterol was observed with SC but not with CA in patients with CKD. Treatment with SC reduced serum phosphate, calcium phosphate, and FGF‐23 levels and there was no change with CA treatment. The inflammatory markers IL‐8, IFN‐γ, and TNFα decreased with response to both treatments. The levels of IL‐6 significantly increased with CA treatment and no change was observed in the SC treatment group. SC showed favorable effects on anti‐inflammatory and vascular calcification biomarkers compared to CA treatment in patients with CKD stages 3 and 4 with normal phosphorous values.